Tex. Act of Apr. 12, 1871, as codified in Tex. Penal Code (1879). Art. 163. - (:unkn) unknown (My University, 1871)
Prohibited the carrying of a concealed or open gun, pistol, Bowie knife, or other dangerous weapon within a half mile of a polling site on an election day. Also prohibited generally carrying a pistol, dirk, dagger, slungshot, sword cane, spear, brass knuckles, Bowie knife, or other kind of knife used for offense or defense. Punishable by fine and forfeiture of the weapon.
Keywords: CARRY; CARRY - CERTAIN PUBLIC PLACES